THE IMPACT OF EXTRINSIC MOTIVATION ON THE TENDENCY TO ETHICAL DEVIATION AMONG YOUNG ATHLETES - moh.ali kuncoro; Himawan Wismanadi; Noorje Anita Kumaat; Moh Turi (Program Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to analyze the relationship between extrinsic motivation and deviance behavior in sports, especially in young athletes. The main issue raised is how external reward-based motivations, such as financial and social recognition, can increase athletes' tendency to engage in deviant behaviors such as manipulation of match results, doping use, and non-compliance with coaches. This type of research is quantitative with a correlational approach, using a cross-sectional research design. The population in this study is young athletes from various sports in Indonesia, with a sample of 200 athletes selected purposively. The instrument used in this study is a questionnaire that measures extrinsic motivation and deviance behavior. The data collection technique was carried out through the distribution of questionnaires directly to respondents. The statistical analysis used was a multiple linear regression test to test the relationship between the free variable and the bound variable. The results showed that extrinsic motivation was significantly related to non-compliance with the coach β = 0.407, doping use β = 0.258, and manipulation of match results β = 0.315. The conclusion of this study is that extrinsic motivation, especially external pressure and social recognition, has a negative impact on athletes' behavior, so it is important for coaches and sports organizations to prioritize the development of intrinsic motivation to reduce the potential for deviance in sports.